Categorization of Bacterial Pathogens Present in Infected Wounds and their Antibiotic Resistance Profile Recovered from Patients Attending Rizgary Hospital-Erbil - Al-Naqshbandi, Ahmed A.; Hassan, Hedy A.; Chawsheen, Mahmoud A.; Abdul Qader, Haval H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
Wound infection with antibiotic-resistant bacteria can extend a patients’ debility and increase the expense of treatment in the long term; therefore, careful management of patients with wound infections is necessary to avoid complications. The usage of antimicrobial agent is a major factor in resistance development. This study aims to understand the causes of wound infections, as well as the criteria for diagnosing them for more sensible antibiotic prescribing. Samples from 269 wound patients were collected, and cultured for bacterial growth. Gram stain technique, bacterial identification via VITEK 2 compact system were investigated in this study. Gram negative bacteria accounted for 59.15% of the total isolates, while pathogenic gram positive bacteria accounted for 40.85% of total isolates. Escherichia coli and Pseudomonas aeruginosa are the dominant pathogenic gram negative bacteria in wounds, while Staphylococcus aureus, and Staphylococcus epidermidis are the dominant pathogenic gram positive bacteria. Pseudomonas aeruginosa showed 100% resistance to the majority of antibiotic tested, including Ampicillin, Amoxicillin/Clavulanic Acid, Aztreona, Ceftriaxone, and others. Staphylococcus aureus and Staphylococcus epidermidis are 100% resistant to Ampicillin, Ceftriaxone, and Cefotaxime. For more efficient antibiotic prescriptions, the causative microorganisms, and their current susceptibility patterns need to be mandated for testing before prescribing any antibiotics to patients. Prescriptions are frequently based solely on general information about the antibiotic's function, rather than on individual response variation to the pathogen and the antibiotic. Particularly when the common pathogens in this study show multidrug resistance in wounds.